Nonlinear Axion Electrodynamics: Axionically Induced Electric Flares in the Early Magnetized Universe - Alexander B. Balakin (MDPI AG, 2021)
We consider the nonlinearly extended Einstein–Maxwell-axion theory, which is based on the account for two symmetries: first, the discrete symmetry associated with the properties of the axion field, and second, the Jackson’s symmetry, prescribing to the electrodynamics to be invariant with respect to the rotation in the plane coordinated by the electric and magnetic fields. We derive the master equations of the nonlinearly extended theory and apply them to the Bianchi-I model with magnetic field. The main result, describing the behavior of the nonlinearly coupled axion, electromagnetic, and gravitational fields is the anomalous growth of the axionically induced electric field in the early magnetized Universe. The character of behavior of this anomalous electric field can be indicated by the term flare. We expect, that these electric flares can produce the electron–positron pair creation, significant acceleration of the born charged particles, and the emission of the electromagnetic waves by these accelerated particles.